The Effect of Digital Picture Series Media on Simple Essay Writing Skills in Elementary Schools - Trisna Aulia; Vevy Liansari (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine the effect of digital series picture media on simple essay writing skills in the Indonesian language subject for third-grade students at SDN Tawangrejo II Pandaan, classified as low. The research method used in this study is quantitative with a pre-experimental design, specifically the one-group Pre-Test-Post-Test design. The subjects of this study were 32 third-grade students. The sampling technique used in this study was saturated sampling. The data collection technique used in this study was a test to measure third-grade students' simple essay writing skills. The test was conducted with a Pre-Test and a Post-Test. The test consisted of writing a simple essay based on five indicators. The data analysis technique differed significantly between the Pre-Test and Post-Test results. This was indicated by the hypothesis test using the paired sample t-test with a significance value of 0.000, which means the sig value < 0.05. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The use of digital series picture media significantly affects simple essay writing skills.